Pengaruh Pengendalian Internal, Moralitas Individu dan Personal Culture Terhadap Kecurangan Akuntansi - Nur Lazimatul Hilma Sholehah; Syamsuri Rahim; Muslim Muslim (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2018)
This research is a quantitative study to examine the effect of internal control, personal culture morality on accounting fraud. The object of this research is the Gorontalo Province Regional Organization (OPD). Sampling using purposive sampling method through survey method. The results of this study indicate that Internal Control has a negative and significant effect on accounting fraud. Individual morality has no significant negative effect on accounting fraud. Personal Culture has no significant positive effect on accounting fraud.